2014
DOI: 10.1016/j.ibiod.2014.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of decay resistance strategies of durable tropical woods species: Bocoa prouacencsis Aublet, Vouacapoua americana Aublet, Inga alba (Sw.) Wild

Abstract: International audienceThe study of decay resistance in wood is of interest for wood end-users but also for the global carbon balance since wood biodegradation is a key driver of forest ecosystem functioning through its impacts on carbon and nutrient cycling. We studied the density and wood extractive contents in order to understand decay resistance against soil microflora after 90 days exposure of sapwood and heartwood from three Neotropical wood species known for their decay resistance: Bocoa prouacensis, Vou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Durable heartwood had higher extractive content than moderate-durable woods. The higher percentage of extractives in the durable heartwood was expected, as extracts are active to preserve the internal tissue of the tree against interior attack (Amusant et al 2014). These results are supported by previous studies, which showed that very durable and durable tropical hardwood timbers have higher extractives content in the heartwood than moderate and non-durable woods (Lukumandaru 2013).…”
Section: Extraction Yieldsupporting
confidence: 83%
“…Durable heartwood had higher extractive content than moderate-durable woods. The higher percentage of extractives in the durable heartwood was expected, as extracts are active to preserve the internal tissue of the tree against interior attack (Amusant et al 2014). These results are supported by previous studies, which showed that very durable and durable tropical hardwood timbers have higher extractives content in the heartwood than moderate and non-durable woods (Lukumandaru 2013).…”
Section: Extraction Yieldsupporting
confidence: 83%
“…Given the agreement between the range of corrected inn WD and the estimation of corWD ctr observed in P. venosa, we hypothesize that the decrease in the HWD from the pith to the HW/SW boundary might be due to the decrease in total extractive content. Finally, SW also contains extra material such as nonstructural carbohydrates, gums, resins, silicate, or precursors of extractives [37,49,71,72] that may impact SWD. Although it is generally acknowledged that the concentration of extra materials is generally lower in SW than in HW [70], some species may have high extractive content in the SW [36,72].…”
Section: Limitations To the Correction Of Wd By Extractive Contentmentioning
confidence: 99%
“…2006.). To constitute the DEGRAD database, soil tests have been performed incubating wood blocks in French Guiana soils in 2010/2012 in controlled laboratory conditions as mentioned in Amusant et al (2014). Mass losses (%) have been measured after 6 incubation months.…”
Section: Gsts and Wood Durabilitymentioning
confidence: 99%
“…Besides macro and micro-environmental factors, wood intrinsic properties trigger its microbial degradation (Amusant et al, 2014;Valette et al, 2018). Wood natural durability is due to the presence and organization of the recalcitrant polymers (cellulose, hemicellulose and lignin) and also of antimicrobial molecules (wood extracts) (Valette et al, 2017).…”
Section: Gst Reactivity and Wood Densitymentioning
confidence: 99%
See 1 more Smart Citation